VD_FINDINFO Jug / 2016 / 121 vom 30. Oktober 2015 - VD Tribunal cantonal (2015)
RECEL, DISSIMULATION{CHOSES, FAITS}, CONTRAINTE SEXUELLE, VIOL, SURSIS À L'EXÉCUTION DE LA PEINE, IN DUBIO PRO REO, MINISTÈRE PUBLIC | 160 CP, 189 CP, 190 CP, 42 al. 1 CP, 47 CP